Shadow Removal and Contrast Enhancement in Optical Coherence Tomography Images of the Human Optic Nerve Head - Girard, Michaël J. A.; Strouthidis, Nicholas G.; Ethier, C. Ross; Mari, Jean Martial (Investigative ophthalmology & visual science, 2011)
To improve the quality of optical coherence tomography (OCT) images of the optic nerve head (ONH). Two algorithms were developed, one to compensate for light attenuation and the other to enhance contrast in OCT images. The former was borrowed from developments in ultrasound imaging and was proven suitable with either time- or spectral-domain OCT. The latter was based on direct application of pixel intensity exponentiation. The performances of these two algorithms were tested on spectral-domain OCT images of four adult ONHs. Application of the compensation algorithm significantly reduced the intralayer contrast (from 0.74 ± 0.16 to 0.17 ± 0.12; P < 0.001), indicating successful blood vessel shadow removal. Furthermore, compensation dramatically improved the visibility of deeper ONH tissues, such as the peripapillary sclera and lamina cribrosa. Application of the contrast-enhancement algorithm significantly increased the interlayer contrast (from 0.48 ± 0.22 to a maximum of 0.89 ± 0.05; P < 0.001) and thus allowed a better differentiation of tissue boundaries. Contrast enhancement was robust only when compensation was considered. The proposed algorithms are simple and can significantly improve the quality of ONH images clinically captured with OCT. This study has important implications, as it will help improve our ability to perform automated segmentation of the ONH; quantify the morphometry and biomechanics of ONH tissues in vivo; and identify potential risk indicators for glaucoma.